THEDIFFERENTROLESOFINVOLVEMENTWITHINCORPORATE AND PRODUCT ADVERTISEMENTS - Raja Sharah Fatricia (DIGEST MARKETING, 2012)
Corporateadvertisementsareofgrowinginterestforcompanies,besidesthattheroleofinvolvementisofgrowinginterestbecausenewmediamakesithardertogetconsumersinvolvedwithamarketingmessage.Thispaperexploresaliteraturereviewoninvolvementandcorporateadvertisementasthereislittletonoresearchdoneonthistopic.Basedontheanalysisitcanbeconcludedthatadvertisinginvolvementisofhighrelevancewithincorporateadvertising,andhasalargerinfluenceonadoutcomesthanpredispositionalinvolvement.Predispositionalinvolvementonlyinfluencescorporateadvertisementoutcomeswhenmediatedbyadvertisementinvolvement.Thusformarketersdevelopingcorporateadvertisements,creatingadvertisementinvolvementisespeciallyimportant.Keywords:Roleofinvolvements,corporateadvertisements,productadvertisements,advertisinginvolvement